The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/frsc.2021.648473
|View full text |Cite
|
Sign up to set email alerts
|

Positive Energy District: A Model for Historic Districts to Address Energy Poverty

Abstract: The Positive Energy District (PED) concept has been pointed out as key for cities' energy system transformation toward carbon neutrality. The PED may be defined as an energy-efficient and flexible urban area with net-zero energy import and greenhouse gas emissions, aiming toward annual local surplus of renewable energy. Most of the studies and practical experiences about PEDs are based on newly built districts, where the planning and integration of innovative solutions are less complex and more cost-effective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…At present, many scholars have conducted research on carbon emission, including the measurement and evaluation , dynamic change (Cheng et al, 2018b), influencing factors and effects analysis (Xu et al, 2021;Zhang H et al, 2021) of carbon emission efficiency. Scholars think that policy and supervision (Calvo et al, 2021;, technological innovation (Gouveia et al, 2021;He et al, 2021;Wu H et al, 2021;Wyse et al, 2021;Xie et al, 2021), human capital (Song et al, 2020), industrial structure (Cheng et al, 2018a;Wu L et al, 2021) and urbanization (Sun and Huang, 2020;Wang F et al, 2021) will affect carbon emission efficiency. and Meng et al (2016) used DEA model to measure the carbon emission efficiency of 42 thermal power plants and 30 provinces in China from the micro and macro levels respectively, and found that there was regional imbalance in China's carbon emission efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, many scholars have conducted research on carbon emission, including the measurement and evaluation , dynamic change (Cheng et al, 2018b), influencing factors and effects analysis (Xu et al, 2021;Zhang H et al, 2021) of carbon emission efficiency. Scholars think that policy and supervision (Calvo et al, 2021;, technological innovation (Gouveia et al, 2021;He et al, 2021;Wu H et al, 2021;Wyse et al, 2021;Xie et al, 2021), human capital (Song et al, 2020), industrial structure (Cheng et al, 2018a;Wu L et al, 2021) and urbanization (Sun and Huang, 2020;Wang F et al, 2021) will affect carbon emission efficiency. and Meng et al (2016) used DEA model to measure the carbon emission efficiency of 42 thermal power plants and 30 provinces in China from the micro and macro levels respectively, and found that there was regional imbalance in China's carbon emission efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, LECs can potentially provide free or reduced cost energy and an additional income stream (should energy be sold) for those in energy poverty. On a PED scale, research in Portugal indicates the potential of PEDs as a tool for mitigating energy poverty in the historic district of Alfama in Lisbon [39].…”
Section: Legally Permitted Activities In Energy Sectormentioning
confidence: 99%
“…Civiero et al [15] provide a view of a district simulation model able to analyze a reliable prediction of potential business scenarios on large scale retrofitting actions and to evaluate a set of parameters and co-benefits resulting from the renovation process of a cluster of buildings. Gouveia et al [16] also argued that the transformation of the existing districts is essential, including historic districts, which present common challenges across EU cities, such as degraded dwellings, low-income families, and gentrification processes due to massive tourism flows. In their report, they discussed how the PED model can be an opportunity for historic districts to reduce their emissions and mitigate energy poverty.…”
Section: Introductionmentioning
confidence: 99%